1990
DOI: 10.1042/bj2700017
|View full text |Cite
|
Sign up to set email alerts
|

Macromolecular association of ADP-ribosyltransferase and its correlation with enzymic activity

Abstract: The macromolecular self-association of ADP-ribosyltransferase protein in solution was studied by several experimental techniques: quantitative gel filtration, electrophoretic analyses in non-denaturing gels, and cross-linking the enzyme protein with glutaraldehyde, dimethyl pimelimidate, dimethyl suberimidate, dimethyl 3,3'-dithiobisproprionimidate and tetranitromethane. The self-association of the polypeptide components obtained by plasmin digestion was also determined by using the above cross-linking agents.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(39 citation statements)
references
References 37 publications
4
35
0
Order By: Relevance
“…PARP1 dimerisation at sites of DNA damage has been implicated in multiple previous studies of PARP1 activation 1,7,[26][27][28] , although this has not been universally observed 20,21 .…”
Section: Dna Damage-dependent Dimerization Of Parp1-dbdmentioning
confidence: 99%
See 1 more Smart Citation
“…PARP1 dimerisation at sites of DNA damage has been implicated in multiple previous studies of PARP1 activation 1,7,[26][27][28] , although this has not been universally observed 20,21 .…”
Section: Dna Damage-dependent Dimerization Of Parp1-dbdmentioning
confidence: 99%
“…A substantial body of data suggest that PARP1 becomes activated at sites of DNA damage by trans-modification of one PARP1 molecule by another, with formation at least transiently, of a dimeric interaction between DNA-bound PARP1 molecules 1,7,[26][27][28] . Two recent studies 20,21 , while observing DNA binding modes consistent with dimerization or oligomerization in some circumstances, were able to define buffer conditions and DNA molecules in which 1:1 protein:DNA complexes predominated.…”
Section: Europe Pmc Funders Author Manuscriptsmentioning
confidence: 99%
“…PARP-1 self-association is linked to maximal DNAdependent enzyme activation (12), and several regions of PARP-1 are known to form interdomain contacts (12,41,42,46). Kinetic analysis of PARP-1 activity and the stoichiometry of PARP-1 binding to DNA indicate that PARP-1 is a catalytic dimer (22,37).…”
Section: Discussionmentioning
confidence: 99%
“…DNA strand breaks stimulate PARP-1 automodification, and activated PARP-1 recruits DNA repair factors to the site of DNA damage to facilitate repair (10,11). There are several factors that control PARP-1 activity, including self-association, interaction with histones and nucleosomes, NAD ϩ concentrations, structure-specific binding to DNA, and automodification (1)(2)(3)12). However, there are few molecular level insights into mechanisms that control PARP-1 activity.…”
mentioning
confidence: 99%
“…It is of interest that DEP reacts with only two histidine residues of the 56 kDa polypeptide but not with imidazole molecules present in the 29 kDa polypeptide domain. This apparent selectivity is unexplained, unless one considers macromolecular structural factors such as dimerization [18] that may determine this selectivity towards DEP under given experimental conditions. Our results thus provide preliminary evidence for the localization of the catalytic site of ADPRT in the 56 kDa carboxy-terminal polypeptide domain, coinciding with a previous suggestion [19], which is based on specific thiol labelling of ADPT.…”
Section: Discussionmentioning
confidence: 99%